9/11 and the emergence of critical terrorism studies - Da Silva, R. (2021)
The attacks of 11 September 2001 have profoundly impacted the field of terrorism studies. In this article we aim to trace, in particular, the impact of this date on the establishment of critical terrorism studies (CTS) as a school of thought. Such an endeavour aims to create an ‘umbrella-term’ to gather scholars from diverse backgrounds, in an attempt to provide a counternarrative to the dominant, mainstream understanding of terrorism and counter-terrorism. CTS scholarship offers alternative approaches to state-centred, ahistorical, and ‘problem-solving’ standpoints, which have been at the origin of numerous atrocities committed, for example, under the Global War on Terror banner. This article explores the key debates stirred by CTS scholarship over the years, its recent advancements, and existing gaps.